Diálogos sobre a biblioteca escolar : entre textos e contextos - Silva, Eduardo Valadares da (2015)
The objective is to understand the behavior of School Librarianship theme, taking as main source the works presented in the Brazilian Congresses of Librarianship, Documentation and Information Science (CBBDs) between 2005 and 2013, and the working method of a school librarian, through the systematic monitoring of their daily activities in relationship with students, teachers and pedagogues, using as context the elementary Municipal School Aristóbulo Barbosa Leão, Vitória-ES. Methodologically we systematized into two distinct periods: the first one occurs through a bibliographical research, called the State of Knowledge about the School Librarianship in Brazil, which is based in the 91 works on school library presented at the XXI, XXII, XXIII, XXIV and XXV CBBDs; the second was made according to collaborative research that accompanies the activities carried out in relation to “schoollibrary-librarian” in the elementary schools of the municipality of Vitória-ES. It was used the texts of Certeau, to demarcate the conceptions of place, space, tactics, strategies and uses, and those of Campello, to understand the state of the art about the school library between 1960 and 2011. We concluded that reading, as well as other possibilities, is the main focus of the papers presented at the CBBDs and the main goal of the librarian followed in the accomplishment of their daily professionals tasks, that are materialized through activities that use resources as music, hip-hop music, the visual arts, the storytelling, poetry and the occupation of the library, according to the wishes of its subject practitioners, aiming with that to break the silencing of this space. Notes, moreover, that it is necessary to perform a job more articulate between librarians and other educators from school, since punctual and fruitful partnerships among those subjects were found and could be expanded to the entire school. In addition, advocates the need for permanent reinvention of space of school library to meet the expectations of its users.